This action might not be possible to undo. Are you sure you want to continue?

1.

The polynomials f(x) and g(x) are defined by

f(x) = x3 + px2 – x + 5 g(x) = x3 – x2 + px +1

where p is a constant. When f(x) and g(x) are divided by x – 2, the remainder is R in each case. Find the values of p and R

2.

The polynomial p(x) = x3 – 4x2 + 2x + k has (x – 2) as a factor.

(a)

Find the value of k,

(b)

Calculate the remainder when p(x) is divided by (x + 3).

(c)

Find the exact values of the roots of the equation p( x) = 0.

3.

The polynomial p(x) is given by p(x) = (x + 3)(x – 2)(x – 4)

(a)

Find the remainder when p(x) is divided by (x + 1).

(b)

(i)

70 A B C + + Express ( x + 3)( x − 2)( x − 4) in the form x + 3 x − 2 x − 4 .

(ii)

70 5 Hence, prove that ( x + 3)( x − 2)( x − 4) dx = N ln 3 – M ln 2 ,

∫

6

where N and M are positive integers.

R = –1 2. (a) k=4 . (c) Simplify the following algebraic fraction as far as possible: x 3 − 3x + 2 x2 −1 5. Express p(x) as the product of three linear factors. (ii) Solutions 1. or otherwise. The polynomial p(x) is given by p(x) = x3 – 4x2 + 3x. (a) (b) Find the remainder when p(x)is divided by x + 1. express p( x) in the form (x – 2)(x2 + ax + b) + r where a. Using algebraic division. (c) (i) Use the Remainder Theorem to find the remainder. b and r are constants. r. p = – 3. Given that x + 2 is a factor of p(x). (a) (b) Use the Factor Theorem to show that x – 3 is a factor of p(x). The polynomial p(x) is given by p(x) = x3 − 3x + 2. when p(x) is divided by x – 2. express p(x) as a product of linear factors.4.

(b) –65 is remainder (c) x = 1 ± √3 3. B = -7. C = 5 (ii) 11 ln 3 – 15 ln 2 4. (a) 30 (b) (i) A = 2. (a) 4 2 (b) (x + 2)(x – 1) ( x + 2)( x – 1) ( x + 1) (c) 5. (a) p(3) = 0 ⇒ x – 3 is a factor (b) p( x) = x( x − 1)( x − 3) (c) (i) – 2 (ii) a = –2 b = –1 r = –2 .

Sign up to vote on this title

UsefulNot usefulC4_Algebra_Questions

C4_Algebra_Questions